PENGARUH INVESTASI DAN PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN BERAU - Abdul Hakim (ECO-BUILD, 2025)
The objective of this study is to determine: (1) the influence of Foreign Direct Investment (FDI) on economic growth in Berau Regency, (2) the influence of Domestic Investment (DI) on economic growth in Berau Regency, (3) the influence of Regional Original Revenue (ROR) on economic growth in Berau Regency, and (4) the combined influence of FDI, DI, and ROR on economic growth in Berau Regency. The sampling method used in this study is non-probability sampling, with a purposive sampling technique for selecting the samples. Data collection methods include literature review and documentation.The results of this study reveal the following: (1) FDI significantly influences economic growth in Berau Regency, as evidenced by the t-table value of 12.687 being less than the t-count value of 15.776. (2) DI significantly influences economic growth in Berau Regency, as evidenced by the t-table value of 12.687 being less than the t-count value of 12.743. (3) ROR significantly influences economic growth in Berau Regency, as evidenced by the t-table value of 12.687 being less than the t-count value of 18.551. (4) FDI, DI, and ROR collectively have a significant influence on economic growth in Berau Regency, as indicated by the F-count value of 86.042, which is greater than the F-table value of 4.76, and a significance value (0.000) that is smaller than the probability value (0.05).